DURAÇÃO DA QUALIDADE DE OVOS ESTOCADOS DE POEDEIRAS COMERCIAIS DE DIFERENTES IDADES - MENDONÇA, Ana Paula Vargas; MARCELO, Gislaine de Castro; LONGO, Luise Fernanda da Rocha; SANTANA, Patrícia Gomes; BAIRROS, Eliane Corrêa; GARCIA, Elis Regina de Moraes (ANAIS DO ENIC, 2023)
-